2003
DOI: 10.1002/etc.5620220429
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cellular energy budget as a measure of whole effluent toxicity in zebrafish (Danio rerio)

Abstract: Organisms exposed to suboptimal conditions face an a priori cost of combating stress in terms of metabolic resources. The energy available for maintenance, growth, and reproduction, based on the biochemical analysis of the energy budget rather than on the direct measurement of those endpoints, may therefore provide a sensitive measure of stress in an organism. The aim of this study was to validate changes in energy budget as an ecologically relevant sublethal parameter by comparing these responses with physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(44 citation statements)
references
References 47 publications
3
36
1
2
Order By: Relevance
“…Under stress PROT content can either increase or decrease. Smolders et al (2003) reported that low to intermediate levels of pollution trigger increased protein synthesis (e.g. metabolic defenses involved in detoxification processes), but decreased protein synthesis was also referred, being attributed to high concentrations of pollutants (Smolders et al, 2004), when organisms cannot handle oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Under stress PROT content can either increase or decrease. Smolders et al (2003) reported that low to intermediate levels of pollution trigger increased protein synthesis (e.g. metabolic defenses involved in detoxification processes), but decreased protein synthesis was also referred, being attributed to high concentrations of pollutants (Smolders et al, 2004), when organisms cannot handle oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Under stress, hepatic glycogen rapidly provides glucose, via glycogenolysis pathway, which supplies other organs readily usable energy (Moon and Foster 1995). Moreover, a decrease in lipid stores and the disruption of lipid metabolism were shown for several pollutants and fish species (Smolders et al 2003;Zheng et al 2013;Castelli et al 2014). Modification in the protein concentration results from a perturbation in the protein turnover, with an imbalance between the synthesis and the degradation rate of proteins (Smolders et al 2003).…”
Section: Physiological Responses To Pesticide Exposure and Temperaturmentioning
confidence: 99%
“…Moreover, a decrease in lipid stores and the disruption of lipid metabolism were shown for several pollutants and fish species (Smolders et al 2003;Zheng et al 2013;Castelli et al 2014). Modification in the protein concentration results from a perturbation in the protein turnover, with an imbalance between the synthesis and the degradation rate of proteins (Smolders et al 2003). In the white muscle, proteins are the main source of energy.…”
Section: Physiological Responses To Pesticide Exposure and Temperaturmentioning
confidence: 99%
“…If the former, it is unknown whether this was due to a reduction in mnemiopsin through protein degradation, loss through membrane damage, or a reduction in mnemiopsin synthesis as toxic exposure resulted in prioritizing other cellular functions such as repair and detoxification pathways (e.g. Camus et al 2003, Smolders et al 2003, Olsvik et al 2012. If mnemiopsin activity was affected, there may have been a reduction in binding or light production efficiency, either through direct toxic effects or indirectly (e.g.…”
Section: Discussionmentioning
confidence: 99%